Company boards : their responsibilities to shareholders, employees, and the community - Shenfield, Barbara Estelle; Political and Economic Planning (London : Allen and Unwin [for] Political and Economic Planning, 1971)
The book elucidate the problems of the responsibilities of company boards of directors, towards shareholders, employees and the community.
Includes bibliographical references.
sju 24/01/2019
Loans
Keywords: Industries; Directors of corporations